Integration of Chiropractic Services in Military and Veteran Health Care Facilities: A Systematic Review of the Literature. (April 2016) - Green, Bart N.; Johnson, Claire D.; Daniels, Clinton J.; Napuli, Jason G.; Gliedt, Jordan A.; Paris, David J.
This literature review examined studies that described practice, utilization, and policy of chiropractic services within military and veteran health care environments. A systematic search of Medline, CINAHL, and Index to Chiropractic Literature was performed from inception through April 2015. Thirty articles met inclusion criteria. Studies reporting utilization and policy show that chiropractic services are successfully implemented in various military and veteran health care settings and that integration varies by facility. Doctors of chiropractic that are integrated within military and veteran health care facilities manage common neurological, musculoskeletal, and other conditions; severe injuries obtained in combat; complex cases; and cases that include psychosocial factors. Chiropractors collaboratively manage patients with other providers and focus on reducing morbidity for veterans and rehabilitating military service members to full duty status. Patient satisfaction with chiropractic services is high. Preliminary findings show that chiropractic management of common conditions shows significant improvement.